2021
DOI: 10.3390/rel12050336
|View full text |Cite
|
Sign up to set email alerts
|

StateChurch: Bringing Religion to Public Higher Education

Abstract: Religion undeniably impacts life in modern society in numerous ways. In the U.S., discussions about religion in public life often start at the First Amendment of the U.S. constitution as fundamental to the separation of church and state. Public higher education does not necessarily share established associations with any religion, but is not free from religious influence. Although Christian influences are undeniably present on public campuses, educators hesitate to discuss religion and spirituality due in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…When analyzing how non‐Muslim students responded to these items throughout college, Shaheen et al. (2021) demonstrated growth in the first year of college and across the four collegiate years (see Author in press). Even controlling for different student characteristics and institutional variables, the four items used were reliable measures of appreciative attitudes toward Muslims.…”
Section: Recommendations For Higher Education Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing how non‐Muslim students responded to these items throughout college, Shaheen et al. (2021) demonstrated growth in the first year of college and across the four collegiate years (see Author in press). Even controlling for different student characteristics and institutional variables, the four items used were reliable measures of appreciative attitudes toward Muslims.…”
Section: Recommendations For Higher Education Researchmentioning
confidence: 99%
“…In their landmark longitudinal study of interfaith learning and development (see Rockenbach et al, 2020), Mayhew and Rockenbach (2021) asked students to respond to four statements about seven different religious and nonreligious identities (e.g., Muslim, Buddhist, Jewish) to indicate the degree to which students believed that (1) people in this group make positive contributions to society; (2) individuals in this group are ethical people; (3) they have things in common with people in this group; and (4) they have a positive attitude toward people in this group. When analyzing how non-Muslim students responded to these items throughout college, Shaheen et al (2021) demonstrated growth in the first year of college and across the four collegiate years (see Author in press). Even controlling for different student characteristics and institutional variables, the four items used were reliable measures of appreciative attitudes toward Muslims.…”
Section: Islamophobia and The Appreciation Of Muslimsmentioning
confidence: 99%
“…I begin by establishing the fields most relevant to praxis, then selectively examine key terms within them to identify corresponding constructs, prioritizing relevancy and recency (Maxwell 2006). (1) Religious studies, (2) chaplaincy, and (3) student affairs emerged from the literature (Patel, Peace, and Silverman 2018;Shaheen, Mayhew, and Staples 2021) and from scans of professional organizations' public documents as the fields most engaged in interreligious/interfaith work in U.S. higher education. These are the fields suggesting or defining terms relevant to fostering religious understanding in this context.…”
Section: Problematic Termsmentioning
confidence: 99%
“…The stakes are high: each field has claimed a role in the solution, but none are capable of effecting change single-handedly. Commitment to addressing the problem must include the highest levels of university leadership (Shaheen, Mayhew, and Staples 2021). For religious understanding to become a strategic priority of universities, no one field is likely to be sufficiently convincing on its own.…”
Section: Toward a Common Understandingmentioning
confidence: 99%
“…To shed light on these pressing questions, this paper will explore case studies from various countries, each grappling with the integration of religion in state policy in its own way (Shaheen, Mayhew and Staples, 2021). By examining the diverse approaches and experiences of these nations, we aim to provide insights into the broader challenges and opportunities that arise when multiculturalism meets matters of faith and governance.…”
Section: Introductionmentioning
confidence: 99%